Magisterium - Hirsch, Jeff (New York : Scholastic Press, 2012)
Glennora Morgan's father has been working on a project that will allow him to penetrate the Rift border and retrieve Glennora's mother; but now that he has succeeded the Authority is suddenly trying to kill them both.
Keywords: Conspiracies -- Fiction; Inventions -- Fiction; Escapes -- Fiction; Parent-child relationship -- Fiction; Science fiction